2018
DOI: 10.14336/ad.2017.0902
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pulmonary and Systemic Immunosenescence in Acute Lung Injury

Abstract: Acute lung injury (ALI) is associated with increased morbidity and mortality in the elderly (> 65 years), but the knowledge about origin and effects of immunosenescence in ALI is limited. Here, we investigated the immune response at pulmonary, systemic and cellular level in young (2-3 months) and old (18-19 months) C57BL/6J mice to localize and characterize effects of immunosenescence in ALI. ALI was induced by intranasal lipopolysaccharide (LPS) application and the animals were sacrificed 24 or 72 h later. Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Recent studies reported that inflammatory response played important roles in initiation and maintenance of ALI [46,47]. Pro-inflammatory cytokines such as TNF-α and IL-1β increase the permeability of pulmonary epithelium, furthermore induced lung tissue damage and accumulation of neutrophils which lead to lung edema [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that inflammatory response played important roles in initiation and maintenance of ALI [46,47]. Pro-inflammatory cytokines such as TNF-α and IL-1β increase the permeability of pulmonary epithelium, furthermore induced lung tissue damage and accumulation of neutrophils which lead to lung edema [31].…”
Section: Discussionmentioning
confidence: 99%
“…Immune cell activation is a major mediator of inflammation in ARDS and immunosenescence may impact on the pathogenesis and outcomes in the aged ARDS subpopulation. Experimental murine models of ARDS induced by endotoxin indicate that aged mice display increased bronchoalveolar lavage fluid (BALF) cell counts, protein concentration, and cytokines such as the neutrophil chemoattractant CXCL1/KC in comparison to younger mice (49)(50)(51). Alterations in innate immune cell function, such as macrophage and neutrophils, may contribute to this heightened inflammatory response (52,53).…”
Section: Mechanisms Of Age-dependent Risk and Severity In Ardsmentioning
confidence: 99%
“…Alveolar macrophages (AMs) have increased expression of genes associated with lung injury and fibrosis (54) and defective phagocytic ability (26). In one study of lipopolysaccharide (LPS)-induced acute lung injury (ALI), expression of the M1macrophage markers, CD80 and CD86, were increased in AMs from older mice and in vitro these cells had increased propensity to produce MIP-1α in response to LPS (50). Impairment of antigen presentation in aging macrophages has also been observed and resulting loss of bacterial and viral clearance from the lung could further promote inflammation and damage (55).…”
Section: Mechanisms Of Age-dependent Risk and Severity In Ardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total protein concentration of the supernatant of the lung homogenate was examined with the Pierce TM BCA Protein Assay Kit (Thermo Fisher Scientific, Waltham, MA, USA). The cytokine concentration was then analyzed with the LEGENDplex bead array ELISA (# 740621, BioLegend, San Diego, CA, USA) according to the supplier's manual and as described previously [39]. Cytokine measurements (pg/mL) were then normalized to the total protein concentration (mg/mL) to pg/mg.…”
Section: Cytokine Expression In Lung Tissuementioning
confidence: 99%